ANALISIS PENGARUH PENGEMBANGAN KARIR, KETERLIBATAN KERJA DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI DENGAN KOMITMEN ORGANISASIONAL SEBAGAI MEDIASI (STUDI PADA DINAS PENDIDIKAN KABUPATEN REMBANG) - Atit Ismadiyah, 1142020135 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine and analyze the effect of career development , job involvement and job characteristics on employee performance with organizational commitment as mediation . This research was conducted at the District Education Office employee at Apex s status as a civil servant (PNS) which amounts to 128 people . The sampling technique using purposive sampling method , the method of sampling using the specified criteria . The number of samples in the study amounted to 102 respondents . The results of the analysis and discussion showed that career development not effect on organizational commitment, job involvement positive and significant effect on organizational commitment, job characteristics and not effect on organizational commitment , career development not effect on employee performance , job involvementÂ positive andÂ significant effect on employee performance , job characteristics positive and significant effect on employee performance and Organizational Commitment positive and significant effect on performance . The test results showed that the mediation of organizational commitment is not proven to be mediating variables influence career development , job involvement and job characteristics on employee performance . Keywords : career development , job involvement , job characteristics , organizational commitment , performance